2017
DOI: 10.1177/0030222817691286
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Racial and Ethnic Disparities in Advance Care Planning Using the Integrated Behavioral Model

Abstract: Purpose To explain and predict racial or ethnic disparities in advance care planning (ACP) behaviors among American adults by using the Integrated Behavioral Model (IBM) and the Precaution Adoption Process Model. Methods A randomized, observational, nonexperimental, cross-sectional study design was used to survey American adults between 40 and 80 years of age ( n = 386). Results The majority of respondents (75%) had not completed ACP. Significant differences were found by race or ethnicity: 33% of Whites had c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(68 citation statements)
references
References 50 publications
4
63
1
Order By: Relevance
“…Our findings indicate that African American and Hispanic individuals are less likely to engage in advance care planning, which confirms our third hypothesis. This is consistent with previous research that found that minority groups are less likely to have an advance directive or a healthcare proxy compared to white people (Huang et al, 2016, Institue of Medicine, 2015, Kagawa-Singer and Blackhall, 2001, McAfee et al, 2017). Also, religion is an important determinant of end-of-life planning.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings indicate that African American and Hispanic individuals are less likely to engage in advance care planning, which confirms our third hypothesis. This is consistent with previous research that found that minority groups are less likely to have an advance directive or a healthcare proxy compared to white people (Huang et al, 2016, Institue of Medicine, 2015, Kagawa-Singer and Blackhall, 2001, McAfee et al, 2017). Also, religion is an important determinant of end-of-life planning.…”
Section: Discussionsupporting
confidence: 92%
“…Previous research has highlighted reasons for these racial and ethnic disparities in engaging with advance care planning. Mistrust in healthcare professionals and the health system more generally, perhaps due to previous mistreatment, is a frequently expressed explanation (Institue of Medicine, 2015, Kagawa-Singer and Blackhall, 2001, McAfee et al, 2017). In fact, African Americans are more likely to believe they would be given poorer-quality medical treatment and be treated differently if they completed an advance care directive (Clark et al, 2018, Kagawa-Singer and Blackhall, 2001, McAfee et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Since the mid-1970's, ACP has been promoted as the primary legal means to communicate formally one's healthcare wishes (Sabatino, 2010). In 1990, the federal government passed the Patient Self-Determination Act (PSDA) that promotes one's right for making healthcare decisions by ensuring that individuals' wishes are established, documented, and followed (Detering, Hancock, Reade, & Silvester, 2010;McAfee, Jordan, Sheu, Dake, & Miller, 2017). The PSDA requires any healthcare facility receiving federal funding to inform patients about advance directives-a durable power of attorney for healthcare (DPOAHC) and a living will.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced care planning has been associated with fewer hospitalizations (24) and less stress, anxiety, and depression among family members (25). Hispanics are less likely than non-Hispanic whites to complete an advanced directive and to have discussions with family members and health care professionals about the type of care they want to receive at the (26). This disparity may be due to several factors including a lack of awareness about advanced care resources (26), language barriers and low health literacy (7,27), disagreement about prognosis and care goals between family members or with clinicians (28), and distrust in the medical system because of negative past experiences (29).…”
Section: Discussionmentioning
confidence: 99%
“…Hispanics are less likely than non-Hispanic whites to complete an advanced directive and to have discussions with family members and health care professionals about the type of care they want to receive at the (26). This disparity may be due to several factors including a lack of awareness about advanced care resources (26), language barriers and low health literacy (7,27), disagreement about prognosis and care goals between family members or with clinicians (28), and distrust in the medical system because of negative past experiences (29). The critical role of family in EOL care decision making among Hispanics suggests there is a need for more culturally competent health policies and patient-centered education that facilitate patient and family decision making (5).…”
Section: Discussionmentioning
confidence: 99%